2012
DOI: 10.1016/j.nbd.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction in Parkinson's disease and related disorders

Abstract: Olfactory dysfunction is an early ‘pre-clinical’ sign of Parkinson's disease (PD). The present review is a comprehensive and up-to-date assessment of such dysfunction in PD and related disorders. The olfactory bulb is implicated in the dysfunction, since only those syndromes with olfactory bulb pathology exhibit significant smell loss. The role of dopamine in the production of olfactory system pathology is enigmatic, as overexpression of dopaminergic cells within the bulb's glomerular layer is a common feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
293
0
29

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(331 citation statements)
references
References 374 publications
9
293
0
29
Order By: Relevance
“…Part B of the table: Preferred cutoffs of predictive scores were determined by Youden's index in the discovery cohort and, in a subgroup analysis, did not differ between sexes. SS‐8 = subscore of the eight best‐discriminating odors (licorice, anise, mint, cinnamon, banana, pineapple, rose, and coffee).aResults represent means ± standard deviation; P values calculated using Mann‐Whitney's U test.b P value calculated using chi‐square test.cAdditional lower cutoffs were applied in the distinction versus DDs because a mildly decreased sense of smell had been reported in MSA, PSP, and ET patients2, 5 and our model was established in a comparison of PD patients with HCs (discovery cohort).MMSE, Mini–Mental State Examination; NA, not applicable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Part B of the table: Preferred cutoffs of predictive scores were determined by Youden's index in the discovery cohort and, in a subgroup analysis, did not differ between sexes. SS‐8 = subscore of the eight best‐discriminating odors (licorice, anise, mint, cinnamon, banana, pineapple, rose, and coffee).aResults represent means ± standard deviation; P values calculated using Mann‐Whitney's U test.b P value calculated using chi‐square test.cAdditional lower cutoffs were applied in the distinction versus DDs because a mildly decreased sense of smell had been reported in MSA, PSP, and ET patients2, 5 and our model was established in a comparison of PD patients with HCs (discovery cohort).MMSE, Mini–Mental State Examination; NA, not applicable.…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory deficits affect 75% to 90% of patients with Parkinson's disease (PD), and olfactory testing may also represent a sensitive screening test for individuals at risk of developing PD,1, 2, 3, 4 whereas olfactory function is normal or only mildly impaired in other forms of degenerative parkinsonism or essential tremor (ET) 2, 5. Olfactory testing has recently been incorporated in the newly established International Parkinson and Movement Disorder Society criteria for PD6 and prodromal PD 7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that clinically diagnosed PD is associated with olfactory dysfunction, most using the now common University of Pennsylvania Smell Identification Test (UPSIT) multiple choice test 6, 9. Such testing is critical for assessing olfactory dysfunction, since self‐report can be unreliable 10.…”
Section: Introductionmentioning
confidence: 99%
“…Such testing is critical for assessing olfactory dysfunction, since self‐report can be unreliable 10. However, the only information typically retained from an UPSIT test – the total score – may be a crude measure for guiding diagnosis; while the mean total score of the PD subpopulation is lower than in healthy subjects,9 the sensitivity and specificity of the total score in distinguishing PD from non‐PD‐related olfactory deficits may not be high enough, or early enough in disease progression, to be clinically valuable 11. But what if the pattern of olfactory decline due to PD differs from that due to other age‐related pathologies or to normal aging?…”
Section: Introductionmentioning
confidence: 99%